SYSTEMATIC REVIEW: ANAPLASTIC LARGE CELL LYMPHOMA FOLLOWING BREAST IMPLANT SURGERY - Eveline, Kezia; Lestari, Rizqi Shabrina; Beta Subakti Nata’admadja; Adzalika, Lavonia Berlina (Jurnal Rekonstruksi dan Estetik, 2023)
Highlights: BIA-ALCL, a T-cell lymphoma associated with breast implants, is posing a growing medical challenge due to the increasing use of implants for cosmetic and reconstructive purposes The majority of BIA-ALCL cases were associated with cosmetic reasons for breast implants, and textured implants were predominantly implicated. Abstract: Introduction: BIA-ALCL, a T-cell lymphoma associated with breast implants, poses a growing medical challenge despite its relatively low occurrence, due to the increasing use of implants for cosmetic and reconstructive purposes. Our objective is to review the incidence, characteristics of patients, implant types, management, and outcome of BIA-ALCL. Methods: Pubmed and Science Direct databases were searched to identify case series and observational research. A systematic review was conducted by looking up the keywords "breast implant” and "anaplastic large cell lymphoma”. Result: 11 relevant articles were assessed. A total of 353 BIA-ALCL cases have been reported. The mean age at diagnosis was 59.6 years. More than half (53.26%) of the reasons for the breast implants in BIA-ALCL patients were cosmetic. The mean time from breast implant placement to diagnosis was 9.99 years. The majority (71.39%) of documented BIA-ALCL cases have been associated with textured devices. BIA-ALCL patients mainly presented with seroma (54.67%). Outcomes included remission (71%), death because of the disease (4.25%), and recurrence (3.96%) with a mean time of duration of follow-up was 2.53 years. Conclusion: BIA-ALCL is rare cancer in some patients with breast implants but is increasing in incidence largely due to consistent and long-term follow-up. It is important for physicians involved in the care of patients with breast implants to be aware of BIA-ALCL and do routine breast exams.